Characterization of real-world clinical and pathological differences between HER2-0 and HER2-low localized breast cancer - Hollmén, Milla; Löyttyniemi, Eliisa; Juhanoja, Eeva; Vihinen, Pia; Sundvall, Maria (Elsevier BV, 2026)
Background: Recent studies suggest that breast cancer patients expressing low levels of human epidermal growth factor receptor 2 (HER2) may benefit from anti-HER2 therapy. Yet, the clinicopathological features of this novel subgroup, known as HER2-low, remain poorly characterized. The aim of this study was to characterize the differences between HER2-negative and HER-low patients.
Methods: This retrospective study included all new localized breast cancer cases diagnosed during 2019 in Southwest Finland. We identified 458 patients, of which 356 were HER2-negative. We further classified HER2-negative patients as follows: HER2 immunohistochemistry (IHC) 0 as HER2-0 and HER2 IHC 1+ or 2+ patients with no amplification by in situ hybridization as HER2-low.
Results: Out of the 378 HER2 non-amplified tumors, 26% (n = 100) were HER2-0 and 74% (n = 278) were HER2-low. Compared to HER2-0, HER2-low patients had fewer comorbidities (p = 0.030) and were more often diagnosed asymptomatically via screening (p = 0.012). HER2-low tumors exhibited lower histological grade (p = 0.021), higher hormone receptor (HR) expression levels (ER: p = 0.0003; PR: p = 0.001) and lower proliferation rates (p = 0.005) than HER2-0 tumors. In HR+ patients, HER2-low was associated with superior OS in stage 2 (p = 0.028) and stage 2a disease (p = 0.004), as well as in patients with 1-2 metastatic lymph nodes (OS: p = 0.006, DFS: p = 0.044). Multivariable analyses performed in all stage 2a patients revealed that HER2-status remained an independent predictor of OS when adjusting for age (≥65 vs. <65 years), detection method, multifocality and administration of adjuvant radiotherapy.
Conclusion: HER2-low patients are characterized by beneficial clinical and pathological features that differ significantly from HER2-0 patients. In the HR+ population, HER2-low is associated with improved survival in breast cancer with locally advanced early-stage disease.